Tertiary Sequence Stratigraphy of Bird Head Area, Eastern Indonesia - Alam, Syaiful; Setiadi, Djadjang Jedi (Geological Agency, 2019)
DOI: 10.17014/ijog.6.3.267-278 A long depositional period of Papua limestone called Kais Formation, which is overlain by clastic sediments of Steenkool Formation, reflects an interesting stratigraphic architecture in the West Papua region. Using seismic stratigraphic method of five stacking patterns, forestepping, downstepping, upstepping, backstepping, and seismic facies (parallel, prograding clinoform, channel fill, mounded) have been observed. Chronostratigraphic reconstruction was completed to figure out the depositional units in space and time. This study reveals the lowstand deposit during Early to Middle Eocene (LST), transgressive-highstand carbonate deposit during Middle Eocene to Middle Oligocene, and transgressive-highstand silisiclastic (TST-HST) deposit during Middle Miocene - Late Pliocene. Â